A 1-m Foucault pendulum rolling on a ball - Salva, Horacio Ramon (2013)
We have built a short Foucault pendulum of 1-m length. The aim of this work was to increase the sensitivity to elliptical trajectories from other longer pendula. The design was a semi-rigid pendulum that rolls over a small ball. The measurements of the movements (azimuth and elliptical trajectory) were done by an optical method. The resulting pendulum works in a medium satisfactory way due to problems of the correct choice of the mass of the bob together with the diameter of the supporting ball. It is also important to keep the rolling surface very clean.